On economic benefits and fiscal requirements of moving from unfunded to funded pensions - Holzmann, Robert (UN ECLAC SantiagoCL, 1997)
Presents the potential benefits of a move from unfunded to funded provisions. Highlights the links between stocks and flows and outlines the main financing options. Summarises empirical evidence of the Chilean pension reform and its impact on economic growth, capital formation and saving.